GAMBARAN PENGETAHUAN MENYIKAT GIGI DAN SKOR DEBRIS PADA SISWA KELAS VII SMP MUHAMMADIYAH 1 KALIBAWANG KULON PROGOThe most common teeth problem in Indonesia is teeth loss because by caries. One of cause caries is debris. Debris is food residue left in the - Anita Anita; Siti Sulastri; Taadi Taadi (Journal of Oral Health Care, 2017)
The most common teeth problem in Indonesia is teeth loss because by caries. One of cause caries is debris. Debris is food residue left in the mouth cavity that is actually can be cleaned naturally by saliva fluid, movement muscles of the mouth and can be cleaned by rinsing and brushing them. Brushing teeth is one of the procedures to keep teeth and mouth clean. According to the report in 2013 from the household health survey of Ministry Of Health mentions the percentage of the Indonesia population who brush their teeth every day during shower is 76,6 %. Indonesian population aged 10 years and over who have a habit of brushing their teeth properly in only 2,3 %. This can be happened because of the knowledge of the people there to maintain the dental health is still very low. This study aims to describe the knowledge brushing teeth and scores debris in 7th grade of Junior High School Muhammadiyah 1 Kalibawang Kulon Progo. This research is descriptive research. The research result shows that 50% student have moderate level of brushing teeth knowledge. About 33% have low knowledge level and 17% have high knowledge level. The average debris score of students are 1,05 with fair criteria. 55% students have debris score in fair criteria, 41% students have debris score in good criteria and 4% students have debris score in poor criteria. The conclusion gained is that most of student in 7th grade of Junior High School Muhammadiyah 1 Kalibawang Kulon Progo have moderate level of brushing teeth knowledge. It was in the amount of 50%. Debris score students in the fair level with average 1,05. It was in the amount of 55%